Landscape works with Piet Oudolf and LOLA : in search of Sharawadgi - Kloe, Fabian de 1982-; Veenstra, Peter 1980-; Vossebeld, Joep; Weeren, Brigitta van 1986-; Oudolf, Piet 1944- (nai010 publishers, 2021)
'In Search of Sharawadgi' presents the ideas and dreams of Piet Oudolf and LOLA Landscape Architects. Piet Oudolf is the Netherlands' most well-known garden designer and he has completed such famous projects as the High Line in New York. This book takes the reader on a journey, showing them how public gardens and landscapes across the world have been transformed. Form the High Line in New York, the gardens of Hauser & Wirth in Somerset, the Star Maze in Tytsjerk to the Leisure Lane in Parkstad. Familiarise yourself with Oudolf's and LOLA's ultimate vision for the future: a global forest against the warming of the earth. A dream that can start in anyone's garden, however big or small. On this journey we are accompanied by the artists Joseph Beuys, Anne Geene, Geert Mul, Sanne Vaassen, Giuseppe Licari and Darcy Neven. With new and existing work, they present us an extraordinary perspective on the discipline of garden design, and major issues such as global warming and the impact of nature on our well-being. Exhibition: SCHUNCK Museum, Heerlen, The Netherlands (02.05.-03.10.2021)
Credits: This publication is an initiative of SCHUNCK in Heerlen, the Netherlands, and was produced to accompany the exhibition "In Search of Sharawadgi: Landscape Works with Piet Oudolf and LOLA". - Ausstellungsdaten ermittelt: 5 June - 17 October 2021
Keywords: Oudolf, Piet -- 1944-; LOLA Landscape Architects; Ausstellungskatalog -- Schunck* -- 05.06.2021-17.10.2021 -- Heerlen; Bildband